2017
DOI: 10.1177/000313481708300423
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications Predict 30-Day Readmission in Geriatric General Surgery Patients

Abstract: The Affordable Care Act has placed unplanned patient readmissions under more scrutiny than ever. Geriatric patients, in particular, suffer a disproportionate amount of complications from any kind of hospitalization, including readmissions. This study seeks to identify risk factors in this population that predispose them to an unplanned readmission within 30 days after index surgery. The National Surgical Quality Improvement Program database was used to select patients 65 years and older, who underwent general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Our study found the strongest association magnitude of postoperative presence of DVT with the unplanned readmission with an adjusted OR of 4.2, which was consistent with a previous finding that DVT increased the risk of postoperative admission within 30 days by 1.9 times in geriatric general surgery patients. 29 In another study of 9441 patients undergoing primary total hip arthroplasty, Mednick et al 30 also observed the same result that postoperative DVT was associated with an increased risk of 30-day readmission. Considering the still very high prevalence rate (21.6%, 201/ 930) of DVT after surgeries in this study, the strongest association with readmission, and the inadequate prophylaxis rate in previous studies, 31 we suggest routine preoperative prophylaxis, early detection, and adequate treatment.…”
mentioning
confidence: 83%
“…Our study found the strongest association magnitude of postoperative presence of DVT with the unplanned readmission with an adjusted OR of 4.2, which was consistent with a previous finding that DVT increased the risk of postoperative admission within 30 days by 1.9 times in geriatric general surgery patients. 29 In another study of 9441 patients undergoing primary total hip arthroplasty, Mednick et al 30 also observed the same result that postoperative DVT was associated with an increased risk of 30-day readmission. Considering the still very high prevalence rate (21.6%, 201/ 930) of DVT after surgeries in this study, the strongest association with readmission, and the inadequate prophylaxis rate in previous studies, 31 we suggest routine preoperative prophylaxis, early detection, and adequate treatment.…”
mentioning
confidence: 83%
“…But we did not find the same attention for elderly people, in which the choice of surgical option instead of the conservative one can be debated. Geriatric patients suffer a disproportionate amount of complications from any kind of hospitalization, including readmissions [12] and the independent risk factors are age, ASA Class > 2, operation time, any complication and deep vein thrombosis [13]. Comorbidities and use of anticoagulant therapy represent an important element in delaying the "definitive" surgical procedure, according to the questionnaire compiled by patients during the follow-up [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In addition, quality measures, such as prolonged hospital length of stay and unplanned readmissions, are more prevalent among patients with multiple comorbidities and those individuals who experience a postoperative complication. [5][6][7] Equally as important, the incidence of perioperative complications may cause a reduction in both quality of life and overall survival. [8][9][10][11] The wideranging impact of postoperative complications underscores the need for appropriate preoperative risk stratification to improve patient selection, and to educate and allow for informed patient consent.…”
mentioning
confidence: 99%